Kemandirian Belajar Menuju Pembelajar Yang Bahagia - Asina Christina Sitio (Jurnal Visi Pengabdian Kepada Masyarakat, 2020)
The spread of COVID 19 throughout the world, especially in Indonesia has changed the way how people live. Some significant changes including medical, education, economy, and social relations. The use of technology and the internet are necessity for people in adapting to the corona viruses’ impact. Indonesia’s government has issued policy to learn from home, so that the face of education in this country has changed significantly. Learning is no longer done in schools building because learning can be done anywhere, anytime, with unlimited learning resources in internet. However, this flexibility in learning has not been supported by the learner readiness in many level of education, including in higher education. There are complaints from student related to the distance learning system. Psychology programs are needed in order to improve students' soft skills in managing their learning to be a self-regulated learner, so that they can manage the obstacles they face, and be happy in undergoing the distance learning process.